INCREASED DENTAL IMPLANT OSTEOINTEGRATION IN MENOPAUSAL OSTEOPOROSIS IN WOMEN - Achilova Nodira Ganievna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Introduction Osteoporosis is a systemic skeletal disease that is accompanied by a decrease in bone density and changes in bone microarchitecture, leading to increased fragility and a high risk of fractures[1][2]. According to WHO data, approximately every third woman and every fifth man over 50 suffers from osteoporosis[1][3]. In Russia, the prevalence of osteoporosis among women after 50 years is 33.8%, among men - 26.9%[1]; the number of diagnosed patients is close to 14 million people[4][3]. In postmenopause in women, calcium leaching from bones accelerates, which is especially relevant for dental implantation: insufficient bone volume of the alveolar ridge can limit the possibility of full-fledged osteointegrative implantation. On the other hand, dental implants are successfully implanted in patients with osteoporosis. Recent publications indicate high survival rates of implants (>90-95%) even in women with osteoporosis[6][7]. Due to the increasing number of elderly patients and the prevalence of osteoporosis, the task of ensuring reliable osseointegration during menopause in women is becoming increasingly important both in maxillofacial surgery and in dental practice. The purpose of this work is to summarize modern data on the impact of osteoporosis (including drug-induced osteoporosis when taking bisphosphonates) on the osteointegration of dental implants in women during the climacteric period and to examine modern approaches (PRGF, osteoplasty, 3D- planning) to treating such patients.